Implementation Of Wokbolic Antenna 433 MHz For Wireless Sensor Network Devices Using The LoRa Protocol - Hadikusuma, Ridwan Satrio; Saragih, Yuliarman; Rahmadewi, Reni (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2024)
Wireless Sensor Network (WSN) is a network consisting of sensor devices capable of detecting the physical condition of the surrounding environment and sending information on the sensor readings to the user for mon-itoring. To be able to transmit data wirelessly, an antenna is needed to be able to transmit signals on the WSN. A wokbolic is a parabolic antenna device that serves to transmit wireless signals. The purpose of this research is to implement the Wokbolic antenna on WSN to analyze the transmission system as an improvement on the existing Wokbolic antenna system. The hardware used in the preparation of this thesis uses the LoRa(Long Range) protocol to transmit the signal further. Implementing a 433 MHz gayabolic antenna using the LoRa protocol on the transmitter side has better transmission results compared to a wireless sensor network using the LoRa protocol without awanbolic antenna. This is evidenced by the comparison of the low RSSI value in the wireless sensor network that implements the wokbolic antenna as its transmission medium with an average RSSI of –65,43 dBm in 40 tests. In testing the transmission system for wireless sensor network devices at a dis-tance of 10.52 km which was tested 40 times, the average value of the delay in the transmission system on the node side that implements the 433 MHz wok antenna is 1014,2 ms. This value is certainly lower than the trans-mission system that does not implement a 433 MHz wokbolic antenna with a delay value of 18134,83 ms.